2014
DOI: 10.9734/ejmp/2014/9216
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Phytochemical Constituents and Antibacterial Potentials of Extracts of Balanites aegyptiaca (Del.) Parts on Antibiotic Resistant Bacterial Isolates

Abstract: This research was carried out in full support of the authors. Author MYT designed the entire study and protocols with interpretations of the results, statistical analyses and prepared the first draft of the manuscript. Author FOI proof read and corrected the draft, authors TBD and GAO helped in the collection and preparations of plant materials. All authors read and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Previous studies revealed the presence of tannin only in Securidaca longepedunculata leaves extracts [16,26]. However, tannin is seldom found in Balanites aegyptiaca extract [13,27]. The effective presence of flavonoids and tannins in the hydro ethanolic extracts would partly explain the therapeutic proprieties of Balanites aegyptiaca, Securidaca longepedunculata an Acacia gourmaensis.…”
Section: Phytochemicalmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies revealed the presence of tannin only in Securidaca longepedunculata leaves extracts [16,26]. However, tannin is seldom found in Balanites aegyptiaca extract [13,27]. The effective presence of flavonoids and tannins in the hydro ethanolic extracts would partly explain the therapeutic proprieties of Balanites aegyptiaca, Securidaca longepedunculata an Acacia gourmaensis.…”
Section: Phytochemicalmentioning
confidence: 97%
“…Recent studies revealed that S. longepedunculata hydro ethanolic extract had an important antifungal activity [10,26]. Likewise, Tula, et al [27] reported that leaves of Balanite aegyptiaca aqueous extracts possessed polyphenols, saponins, steroids, and flavonoids. However, flavonoids and tannins were not found with B. aegyptiaca alcoholic extracts [12,33].…”
Section: Phytochemicalmentioning
confidence: 99%
“…In addition to these chemical compounds, bark contains calcium, iron, phosphorus, sulfur, potassium and manganese were found in stem bark (Gupta et al, 2012). The stem bark contains only flavonoids and polyphenols while the other phytochemicals are found in the others parts of the plant (Tula et al, 2014). Triterpenes, steroïds, sesquiterpens and polysaccharides exert their antiphlogistic activity by intervening in immunological reaction mechanisms (Wagner, 1989).…”
Section: Phytochemicals and Antimicrobial Activitiesmentioning
confidence: 99%
“…Traditionally, water is purified either by adding few herbals like Vetiveria zizanioides, Elettaria cardamom, Ocimum sanctum, Strychnos potatorum, Moringa oleifera (Eze and Ananso;Sathish, and Amuthan. 2012;Wadhwa et al, 2013). The bark of B. aegyptiaca is also used in rural milieu to purify freshwater, and every part of the plant is said to have beneficial properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation